Predictors of treatment allocation guesses in a randomized controlled trial testing double-blind injectable hydromorphone and diacetylmorphine for severe opioid use disorder. (4th July 2017) - Oviedo-Joekes, Eugenia; Marchand, Kirsten; Palis, Heather; Guh, Daphne; Brissette, Suzanne; Lock, Kurt; MacDonald, Scott; Harrison, Scott; Anis, Aslam H.; Krausz, Michael; Marsh, David C.; Schechter, Martin T.
Abstract: Background: SALOME (Study to Assess Longer-term Opioid Medication Effectiveness) tested in a double-blind non-inferiority clinical trial if hydromorphone could be as effective as diacetylmorphine for severe opioid use disorder. Although participants did not guess treatment correctly beyond what is expected by chance, perceived treatment assignment could affect patients' response to treatment. This study tested if treatment allocation guess is associated with treatment outcomes and identified predictors of guess. Methods: Data were obtained through questionnaires and clinical records. Participants were asked what medication they thought they were receiving (diacetylmorphine, hydromorphone or unsure) and their open-ended reasons. Multinomial logistic regression was used to assess the predictors of treatment guess. An inductive thematic analysis was used to code open-ended responses. This clinical trial was registered with U.S. National Institutes of Health (https://clinicaltrials.gov/ct2/show/NCT01447212 ). Findings: Participants referred to prior experiences with opioids and the presence or absence of specific drug effects as reasons for their guesses. There were no differences in illicit opioid use and retention by guess; however those who guessed diacetylmorphine had better physical and mental health scores. Participants with a treatment-related observed drowsiness event, and higher perceived drug-related high scores were more likely to guess diacetylmorphine compared to hydromorphone. Guessing hydromorphone was more likely among those who made negative comments as reasons for treatment guesses. Conclusions: Understanding the clues participants use for treatment allocation guesses and relating them to treatment expectations could be integrated with accurate information about the treatment, providing an opportunity for patient–physician shared decision-making in opioid maintenance treatment. Clinical trial registration: U.S. National Institutes of Health; ClinicalTrials.gov Identifier: NCT01447212;https://clinicaltrials.gov/ct2/show/NCT01447212